Hydroxylation of Apollo 17 Soil Sample 78421 by Solar Wind Protons. Issue 5 (26th May 2021) - McLain, J. L.; Loeffler, M. J.; Farrell, W. M.; Honniball, C. I.; Keller, J. W.; Hudson, R.
Abstract: Hydroxylation by solar wind protons has been simulated in our laboratory on Apollo 17 lunar sample 78421, a very mature regolith sample that is rich with agglutinates (68%). The goal of this study was to determine the rate of hydroxyl formation and their thermal stability by monitoring changes in the SiOH (hydroxyl) stretching band near 3 μm using diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS). A 2 keV H2 + ion beam was used to simulate proton implantation on 78421 and on a crushed fused silica sample. We find that the OH band does not change unless the samples have been annealed in vacuum prior to irradiation. Qualitatively, the OH bands for the fused silica and 78421 are very different. The OH band for fused silica is centered at 2.74 μm and is relatively sharp ranging from 2.67 to 3.1 μm at full width at half maximum (FWHM), while the OH band for 78421 is centered at 3.0 μm and ranges from 2.74 to 3.37 μm at FWHM. The increase in wavelength and broadened nature of the OH band in 78421 may be associated with the OH's proximity to surface defects and/or lattice vacancies. The lack of the H2 O bending mode at 6.1 μm indicates that any adsorbed terrestrial H2 O is below our detection limit, and therefore the H2 O stretching mode at 2.9 μm is not significantly contributing to the broad 3 μm OH band and implies that proton implantation by itself does not lead to water formation. To simulate the maximum dayside temperature on the lunar surface, the lunar sample was heated after proton irradiation. The proton induced OH concentration was reduced by as much as 25% after heating to 400 K (127°C). Plain Language Summary: We performed laboratory experiments to mimic solar wind protons implanting into lunar soils. We measured changes in the OH absorption band near 3 microns using infrared spectroscopy to determine the rate of hydroxyl formation and their thermal stability after proton irradiation. The lunar sample designated 78421, was collected during Apollo 17's manned mission to the Moon. The 78421 sample is composed mostly of clumps of small grains that were exposed to the harsh environment of space. For these experiments, we used a crushed fused silica powder as a control sample for the experiment. Our spectral data shows that the absorption band for OH is much broader for the Apollo sample than for the fused silica control. We did not observe a corresponding bending mode for H2 O at 6.1 μm, which indicates that water is not produced during proton implantation and that the OH stretch near 3 μm is not from adsorbed water. After heating our proton irradiated Apollo soil to 400 K (127°C), the Moon's midday surface temperature, a reduction of up to 25% of the initial OH band area was observed indicating that hydroxyls (or hydrogen) can diffuse in or out of the lunar grains during the day. Key Points: Laboratory measurements show solar wind energy protons produce hydroxyls in Apollo 17 lunar sample 78421 Diffuse reflectance infrared spectra of 78421 show the OH band near 3 μm increases in wavelength and broadens due to space weathering Newly formed hydroxyls diffuse during heating to 400 K, and up to 25% are lost